Potential benefits of near critical and supercritical pre-treatment of lignocellulosic biomass towards anaerobic digestion. Issue 1 (January 2019) - Rosero-Henao, Jenny Carolina; Bueno, Beatriz Egerland; de Souza, Raquel; Ribeiro, Rogers; Lopes de Oliveira, Alessandra; Gomide, Catarina Abdalla; Gomes, Tamara Maria; Tommaso, Giovana
Vegetable crop residues, such as sugarcane bagasse (SCB), despite their limited biodegradability, are potential materials for anaerobic processes because of their low cost, high availability, and sugar content. The difficulty of biodegrading this type of material is primarily related to its chemical composition and to the complex interactions between its compounds (cellulose, hemicelluloses, and lignin). Thus, the following supercritical and near critical carbon dioxide (CO2 ) pre-treatments were evaluated with and without the addition of sodium hydroxide (NaOH): (i) 40°C/70 kgf·cm −2 ; (ii) 60°C/200 kgf·cm −2 ; and (iii) 80°C/200 kgf·cm −2, aiming to enhance the anaerobic biodegradability of SCB. The methanogenic production of SCB increased in all cases in which the material was pre-treated, except the case in which NaOH was used together with a high temperature. The condition using CO2 at 60°C/200 kgf·cm −2 was highlighted with a lignin removal of 8.07% and an accumulated methane production of 0.6498 ± 0.014 LN (273.15K, 1.01325 × 10 5 Pa), 23.4% higher than the value obtained with the untreated material. This condition also showed the highest net energy at the energy balance that was calculated for comparison with the tested conditions. The results showed that pre-treatments with near critical and supercritical fluids have the potential to reduce structural obstacles of lignocellulosic materials and to enhance their anaerobic biodegradability.